Low Vision in Primary Care Optometry - Jose, Randy T; Browning, Robert A; Brilliant, Richard L (Canadian Journal of Optometry, 1982)
A low vision examination procedure has been devised to differentiate those low vision patients who can be helped by the primary care practitioner from those who require referral to a specialized low vision clinic for help via optical aids and/ or rehabilitation.